Peningkatan Kemampuan Komunikasi Matematis Siswa dengan Model Pembelajaran Kooperatif Tipe Make A Match - Septian, Ari; Maghfirah, Destysa; Sumirah, Astri (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2020)
Mathematics is considered difficult and monotonous learning. Therefore it is necessary to apply a variety of learning models. This study aims to determine students' mathematical communication skills, student activities, and student responses. This type of research is Classroom Action Research (CAR). The researcher acts as a teacher in learning by using the Make a Match type of cooperative learning model. Three cycles are carried out, each cycle is held three times, two meetings for the delivery of material using the Make a Match model and the third meeting held a cycle test. This research was conducted at MTs Islamiyah Sayang Cianjur and the students of the VII-D class consisted of 32 students. With sub-subjects Social Arithmetic and Comparison. Based on the research results seen from the average value and the calculation of Classical Absorption Ability of mathematical communication skills of students has increased. Teacher and student activities are included in both categories and have increased and the response of students to learning by using Make a Match is positive. From the results of this study, it can be concluded that the application of the Make a Match type of cooperative learning model in mathematics learning can improve the mathematical communication skills of MTs students.